Return to Snowy River [videorecording (DVD)] - Burlinson, Tom, 1956-; Thornton, Sigrid, 1959-; Dennehy, Brian; Burrowes, Geoff, 1945-; Burrowes, Geoff, 1945-; Burrowes, Geoff, 1945- (Walt Disney Home Video, 2003)
Set in Australia's Victoria Alps, tells the story of a stormy romance caught up in a violent feud between landowners.